The Struggle of Belitung Malay Women and Pragmatic Stilistics in Novel Titled Dwilogy Moon Light (Dwilogi Padang Bulan)" By Andrea Hirata - Rabiatul Adawiyah; Ikhwanuddin Nasution; Siti Norma Nasution; Mulyadi (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
The aim of this study is to describe the reality of fiction, the author's social and global ideas, the shape of the fight of Malay Belitung women, and to examine the novel Dwilogy Moon Light (Dwilogi Padang Bulan) by Hirata's use of pragmatic stylistics. Genetic structuralist theory, liberal feminism, and pragmatic stilistics were all utilised in this work. The genetic structuralism hypothesis is used to assess the truth of fiction, its social context, and the author's point of view. Liberal feminist theory is used to evaluate the forms and elements that contribute to the struggle for Malay Belitung women, while pragmatic stilistics is used to analyze innovative diction, language style, and speech acts. The descriptive qualitative method of analysis is used in this study, along with a heuristic and hermeneutic reading approach. The technique is then applied, with the goal of carefully and thoroughly listening to the contents of the story and then recording complete data in accordance with the formulation of research problems. The findings of this study reveal that (1) fiction is true in terms of themes, characters, and occurrences, grooves, backgrounds, and point of view. Social reality is manifested in the following ways: social processes, social change, social issues, and social structures. The author's world view takes the shape of a relationship between the novel's social setting and the social context of real life, as well as the author's cultural social background and literary work. (2) The Malay Belitung women's struggle takes the shape of a conflict in the fields of honor, economy, and education, and this is the driving force behind the struggle of Malay Belitung women. In novel, gender injustice manifests as marginalization, subjugation, stereotyping, violence, and workload, whereas gender equality manifests as access, participation, and control. (3) Pragmatic Stilistics takes the form of the use of concrete language styles such as special, greeting, connotative, and foreign. Based on the structure of the sentence, including climax, anticlimax, antithesis, and recurrence. Based on the simplest kind of meaning: Litotes, Policyendon, Hiperbola, Metaphor, Allegory, Personification, and Irony. Employing illocutorial speech acts such as aggressive, commanding, expressive, commissioning, and declaring.